2020
DOI: 10.1093/ajcp/aqaa005
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren Syndrome in Primary Salivary Gland Lymphoma

Abstract: Objectives Sjögren syndrome (SS) is considered as a major etiologic factor for primary salivary gland lymphoma (SGL). However, the percentage of SGL that is caused by SS (and thus the real impact of SS on SGL epidemiology) is unclear. We aimed to assess the prevalence of SS in patients with SGL through a systematic review and meta-analysis. Methods Electronic databases were searched for studies assessing the presence of SS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
1
4
0
1
Order By: Relevance
“…The reason for this female predominance may be influenced by the higher rate of SS among women and the known association of salivary gland MALT lymphoma and SS. In salivary gland MALT lymphoma, the prevalence of SS is 33.3% in our study and 29.5%~78% 19,20,22,23 in literature. Multiple salivary glands are involved in eight of 24 patients with SS in our cohort, a similar result reported by Anacak et al 22 …”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The reason for this female predominance may be influenced by the higher rate of SS among women and the known association of salivary gland MALT lymphoma and SS. In salivary gland MALT lymphoma, the prevalence of SS is 33.3% in our study and 29.5%~78% 19,20,22,23 in literature. Multiple salivary glands are involved in eight of 24 patients with SS in our cohort, a similar result reported by Anacak et al 22 …”
Section: Discussionsupporting
confidence: 44%
“…The development of MALT lymphoma is correlated with chronic inflammatory or autoimmune disorders. SS, which is reported in 29.5%–78% cases and 33.3% (24/72) in our cohort, is strongly associated with salivary gland MALT lymphoma 19–23 . Apart from the microbial virulent factors, patients with salivary MALT lymphoma were found to harbor molecular changes including MALT1 translocation, trisomy 3, and trisomy 18, and from the aforementioned aberrations, trisomy 3 was the most commonly detected aberration 11,20 .…”
Section: Discussionmentioning
confidence: 48%
“…We found that Hashimoto thyroiditis and Chlamydia infection were associated with MZL in primary lymphoma of the thyroid and the ocular adnexa, respectively [24,37]. Furthermore, Sjögren syndrome appeared to be almost exclusively associated with MZL in primary salivary gland lymphoma [38]. In our current study, the infectious agent assessed (i.e.…”
Section: Discussionmentioning
confidence: 67%
“…A previous retrospective study has suggested that MALT lymphoma is a significant yet minor portion of pSS in salivary gland lymphoma (12), indicating that MALT lymphoma is one possible rather than the inevitable ending of pSS. Our study determines that even in one individual, the expression profiles in the salivary glands suffering from pSS exhibit heterogenous outcomes as time goes on (Figure 1B).…”
Section: Discussionmentioning
confidence: 98%